2011
DOI: 10.1002/lary.21775
|View full text |Cite
|
Sign up to set email alerts
|

Timing for repair of mandible fractures

Abstract: Complications from repair of mandible fractures are rare; it is difficult to detect significant variables that may impact outcomes. We found no relationship between complications and timing to repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 11 publications
2
23
1
1
Order By: Relevance
“…However, the complication rate we encountered (16.7%) in the delayed group is acceptable. It is in the range of results reported by other teams, whether the patients were treated with early or delayed ORIF [7,[11][12][13][14]. We found no statistical significance between an increased delay from trauma to surgery and occurrence of complication.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…However, the complication rate we encountered (16.7%) in the delayed group is acceptable. It is in the range of results reported by other teams, whether the patients were treated with early or delayed ORIF [7,[11][12][13][14]. We found no statistical significance between an increased delay from trauma to surgery and occurrence of complication.…”
Section: Discussionsupporting
confidence: 56%
“…Some studies even suggest that a slight delay (3-4 days) could allow for better results, as the surgical exposure may be easier after decrease of the facial oedema. Some authors argue that acute injured tissues suffer from restricted vascularization and that the cellular response to trauma is at its maximum between 3 to 4 days [11,15,19]. Furthermore, two studies found that a delayed treatment in selected patients was cost effective, was associated with a shorter stay in hospital and was not associated with a higher rate of complication [18,20].…”
Section: Discussionmentioning
confidence: 98%
“…[18][19][20] A multiple logistic regression analysis by Czerwinski et al confirmed these findings when treatment was delayed beyond 72 hours (Level of Evidence: Risk, III). 21 There is some disagreement when looking at noninfectious complications.…”
Section: Timing Of Repairsupporting
confidence: 50%
“…Barker et al and Lucca et al did not find any statistically significant difference in malocclusion, malunion, nonunion, and dehiscence in early versus delayed repair, but Biller et al reported an increase in marginal mandibular nerve weakness, malocclusion, pain, and noninfectious wound dehiscence requiring tension band removal. [18][19][20] …”
Section: Timing Of Repairmentioning
confidence: 98%
“…The effect of treatment delay on healing of fractures has been a subject of discussion (27). Whereas some studies failed to find any effect of treatment delay on fracture healing (28,29), others reported an increasing number of complications in case of delayed treatment (30,31). A recent systematic review of the literature on the relation between treatment delay and healing complications concluded that there is no strong evidence for either acute or delayed treatment of mandibular fractures in order to minimize healing complications (27).…”
Section: Discussionmentioning
confidence: 99%